"Time series momentum" in commodity markets. Issue 7 (2014) - Julien Chevallier; Florian Ielpo
<x xml:space="preserve"> Abstract </x> Purpose – The purpose of this paper is to contain an empirical application of the concept of "time series momentum" – as developed by Moskowitz et al. (2012) – to commodity markets with daily data during 1995‐2012. Design/methodology/approach – The paper applies the new concept of "time series momentum" to the sphere of commodity markets. Findings – The paper extends the results previously obtained by Moskowitz et al. (2012) to a second category labeled "breakout strategy." Research limitations/implications – Further management strategies can be elaborated for investment management purposes, based on the suggested inclusion of the "time series momentum" in commodities. Practical implications – The empirical evidence gathered in this paper bears practical significance for portfolio managers and commodity tradings advisors relying on trend following strategies. Originality/value – Commodity markets are quickly developing to an alternative asset class for investors. Discovering their properties and characteristics has a broad appeal in finance. <ack> <x xml:space="preserve"> Acknowledgements </x> JEL Classifications — C32; C58; G10; Q02 </ack>